1992
DOI: 10.1037/0022-3514.62.6.958
|View full text |Cite
|
Sign up to set email alerts
|

Explaining our sins: Factors influencing offender accounts and anticipated victim responses.

Abstract: Two studies examined the effects of offender blameworthiness, consequence severity, and offender gender on written accounts provided after a hypothetical predicament. Participants imagined themselves as the offending party in a predicament and provided written accounts after their victims' reproach. Accounts were coded using Schonbach's (1980) account taxonomy. Study 1 results showed that although concessionary strategies were the most prevalent overall, they were more prevalent for more blameworthy offenses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
110
4
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(122 citation statements)
references
References 27 publications
(42 reference statements)
4
110
4
4
Order By: Relevance
“…Experimental studies on the effects of giving different accounts of interpersonal offences have shown the power of apology (Gonzales et al, 1992;Schonberg, 1990;Weiner et al, 1991). When one person apologizes for wronging another, the person hearing the apology can immediately develop a sense of empathy with the difficulty of admitting fault.…”
Section: Some Specific Methods Of Inducing a Sense Of Humilitymentioning
confidence: 99%
“…Experimental studies on the effects of giving different accounts of interpersonal offences have shown the power of apology (Gonzales et al, 1992;Schonberg, 1990;Weiner et al, 1991). When one person apologizes for wronging another, the person hearing the apology can immediately develop a sense of empathy with the difficulty of admitting fault.…”
Section: Some Specific Methods Of Inducing a Sense Of Humilitymentioning
confidence: 99%
“…We combined scenario methodology, which gives control over the transgression and thus increasing internal validity (Aronson, Wilson, & Brewer, 1998), with autobiographical narrative methodology, which is more emotionally involving and has a higher ecological validity (Baumeister et al, 1990;Gonzales, Manning, & Haugen, 1992;Zechmeister & Romero, 2002). In addition to this pluralistic methodological strategy, we sampled both students and employees to test the generalizability of our results.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…When negative partner acts are interpreted as rule violations, they arouse righteous indignation and are construed as betrayals; the positive, relationshiprestoring act that resolves such dilemmas is forgiveness. actions in such a manner as to justify their behavior (e.g., Gonzales, Manning, & Haugen, 1992;Stillwell & Baumeister, 1997). Moreover, victims' desire for revenge and demands for atonement may be met with reciprocal behavioral negativity on the part of perpetrators, in that few perpetrators suffer endless payback and offer bottomless amends (e.g., Hodgins, Liebeskind, & Schwartz, 1996;Ohbuchi et al, 1989).…”
Section: Norm Violations and The Experience Of Betrayalmentioning
confidence: 99%